Teachers’ use of resources in and for mathematics teaching - Grave, Ingvild Lambert; Pepin, Birgit (NOMAD Nordic Studies in Mathematics Education, 2015)
Over the past decades the amount of available resources for mathematics teaching has vastly increased, in particular the availability of resources on the web. However, we know very little about how teachers select and use the available resources. In this paper we investigate how four primary school teachers used curriculum resources in and for their mathematics teaching. Grounded in a case study approach, we have analysed lessons, teacher interviews, and documents they used for their lesson preparation and instruction. Subsequently, we identified five ”usage categories”: (1) resources to manage the teaching objectives; (2) resources to ”inspire” teaching; (3) resources for student work; (4) resources to adapt the teaching to indivi-dual students’ needs (differentiation); and (5) resources to organize the teaching. In this article we explain and discuss these five categories, and argue that the ”lens of resources” offers an opportune window into teachers’ work, in particular their work as mathematics teachers.